Mulgardt's Tower, Court of Abundance (Pacific Novelty Co.)
On verso: It was designed by the master-hand of Louis C. Mullgardt, and is one of the outstanding features among other remarkable architectural masterpieces. Orange trees in bearing are shown in the foreground.